Magnetic flux leakage modelling and optimisation of a CRAHMB for DC motor - Ren, Xiaojun; Le, Yun; Sun, Jinji; Han, Bangcheng; Wang, Kun (IET electric power applications, 2017)
In this study, a combined radial–axial hybrid magnetic bearing (CRAHMB) with four poles is designed for high-speed brushless DC motor. Owing to the small distance of radial and axial unit of CRAHMB, the magnetic flux leakage (MFL) in both radial and axial directions is complex and serious. This study focuses on effective analytical model and optimisation of CRAHMB including flux leakage of permanent magnet circuit and control electromagnetic circuit. MFL analytical model was built based on equivalent magnetic circuit method. Under the condition of satisfying the maximum bearing capacity, the MFL coefficients were optimised with sequence quadratic programming method. A set of optimum parameters were suggested. MFL before and after optimisation are compared by finite element method. Finally, current stiffness calculated with optimised analytical model was verified on a DC motor experiment. The result shows the accuracies of both the axial and radial current stiffness are enhanced.